INTEGRATION OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN LANGUAGE LEARNING: THE CASE OF UZBEKISTAN - Ergashev , Mirjamol (Scientific practical conference, 2026)
The rapid development of digital technologies has transformed education worldwide, particularly in foreign language instruction. Information and Communication Technologies (ICT) provide interactive, learner-centered tools that enhance language learning by offering access to authentic materials, promoting collaboration, and supporting autonomous learning. This study explores the role of ICT in Uzbekistan’s language education system, examining practical applications, pedagogical benefits, and challenges. Digital tools such as multimedia resources, online platforms, mobile applications, and virtual communication technologies support the development of linguistic and communicative competencies. The findings indicate that effective integration of ICT in Uzbek classrooms increases student motivation, improves learning outcomes, and encourages learner independence. The study concludes that ICT has become a crucial component of modern language education in Uzbekistan, requiring teacher training and strategic implementation.